Description of Pseudoechthistatus rugosus n. sp. from Yunnan, China (Coleoptera: Cerambycidae: Lamiinae: Lamiini) - Huang, Gui-Qiang; Yan, Kai; Li, Song (Zootaxa, 2020)
Pseudoechthistatus rugosus sp. nov. is described and illustrated from Yunnan, China.